Is international relations still an American social science discipline in Latin America? - Duarte Villa, Rafael A.; de Souza Pimenta, Marilia Carolina B. [UNESP] (FapUNIFESP (SciELO), 2017)
Over the last 40 years, investigations have shown the discipline of International Relations to reproduce the American influence on its methods, paradigms, and institutional dynamics. This article explores the case for the Latin American community, based on the survey data from the Teaching, Research, and International Politics project (TRIP) 2014 developed by the Institute for the Theory and Practice of International Relations of the College of William and Mary, Virginia (USA). TRIP evaluated International Relations communities in 32 countries around the world. The article aims to answer two main questions: (i) is American influence still dominant over epistemological, methodological, paradigmatic, and institutional representative terms in Latin American International Relations communities, as has been considered in the past? (ii) Is there in the region any contestation to this supposed influence? Primarily, the present article shows an affirmative answer for the first issue. Therefore, and most importantly, the data analysis shows upcoming local pressures rooted in American influence, especially on its epistemic and paradigmatic terms. The data strengthens the miscegenation tendency on its epistemological and paradigmatic aspects, which underlines a lack of consensus over the structure of American dominance over the discipline of International Relations in Latin America, especially if one observes the most numerous and structured group in the region: The Brazilian International Relations community.
Keywords: American influence; International relations; Latin America; TRIP